2017
DOI: 10.1007/s12350-016-0515-2
|View full text |Cite
|
Sign up to set email alerts
|

Computer derived transient ischemic dilation ratio for identifying extensive coronary artery disease using a CZT camera and imaging in the upright position

Abstract: Increased upright TID measurements on a CZT camera are associated with extensive CAD. The upright TID measurements can serve in an adjunctive role to SSS, and may be most effective in patients with a normal upright exercise LVEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Jameria et al reported a reference limit of 1.16 and 1.29 for exercise and pharmacologic normals, respectively. 21 The corresponding TIDr cut-offs were 1.18 and 1.20 in another study by Hu et al . 20 However, numerical differences in the TIDr between our study and the aforementioned papers are expected due to different MPI protocols.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Jameria et al reported a reference limit of 1.16 and 1.29 for exercise and pharmacologic normals, respectively. 21 The corresponding TIDr cut-offs were 1.18 and 1.20 in another study by Hu et al . 20 However, numerical differences in the TIDr between our study and the aforementioned papers are expected due to different MPI protocols.…”
Section: Discussionmentioning
confidence: 90%
“… 4 Furthermore, previous studies have used various criteria to define the ‘normal’ reference population. These include a low (<5%) pre-test probability of CAD, 21 SSS of 3 and below, summed difference score of 1 and below, or an expert interpretation of a normal MPI scan. 20 However, a near normal or normal perfusion does not exclude non-flow limiting CAD.…”
Section: Discussionmentioning
confidence: 99%
“…1) or in a back-leaning sitting position with the back rearward at 30°from vertical, as currently proposed for this camera (Fig. 1) (17).…”
Section: Acquisition and Reconstruction Of Dspect Imagesmentioning
confidence: 99%
“…The mechanisms of this relative increase of measured left ventricular volume at stress have been considered to be an apparent cavity size at stress due to subendocardial ischemia, a true increase in left ventricular volume persisting at the time of post-stress imaging due to stress-induced LV stunning, or a combination of both. 5,6 In this issue of Journal of Nuclear CardiologyÒ, Jameria et al 7 study in detail the TID derivation for the scans obtained with a new Cadmium Zinc Telluride (CZT) camera in the upright position. The TID measurements have not been studied yet on these new cameras.…”
Section: Introductionmentioning
confidence: 99%